RESPIRATORY SINUS ARRHYTHMIA (RSA): NONINVASIVE MEASURE OF PARASYMPATHETIC CARDIAC CONTROL IN NEWLY DIAGNOSED HYPERTENSIVES AND THE INFLUENCE OF ABDOMINAL BREATHING - Srinivasa, J.; Ramesh Bha, M.; Prabha Adhikari, M.R. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Introduction: Respiratory sinus arrhythmia is a valuable  tool for determining autonomic nervous system control of cardiovascular function and an important index of autonomic nervous system pathology Objectives: The present study was conducted to compare the amplitude of respiratory sinus arrhythmia (expressed as Heart rate variability) in normotensive individuals and freshly diagnosed hypertensive subjects and to detect any influence of abdominal breathing in freshly diagnosed hypertensivesMaterials and Methods: 50 Normotensive and 50 age matched hypertensive subjects were selected for the study.The subjects were instructed to breathe normally for first minute then during the second minute , subjects were requested to do conventional deep breathing using chest muscles (Intercostals chiefly). The subjects then performed abdominal breathing during the third minute, while electrocardiogram(ECG)in limb lead was being recorded and changes in heart rate was manually measured.Results: The mean heart rate variability of newly diagnosed hypertensives was 6.30±1.11 for normal breathing, 12.48±1.64 for  conventional deep breathing and 15.56±2.54 for abdominal breathing and mean heart rate variability of normotensive subjects was 8.10±2.25 (P<0.0001) for normal breathing,18.08±5.12 (P<0.0001) for deep breathing using chest muscles and 20.68±6.28 (P<0.0001) for abdominal breathing.Discussion and Conclusion: The newly diagnosed hypertensive subjects had significantly reduced heart rate variability ( amplitude of RSA) compared to age matched controls, which improved with abdominal breathing Thus the deleterious effect of reduced HRV can be revered to an extent through proper abdominal breathing in the hypertensive subjects as well as in  controls as shown in our study.